2017
DOI: 10.1111/micc.12373
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics for investigating vaso‐occlusions in sickle cell disease

Abstract: SCD stems from amutation in the beta globin gene. Upon deoxygenation, hemoglobin polymerizes and triggers RBC remodeling. This phenomenon is central to SCD pathogenesis as individuals suffering from the disease are plagued by painful vaso-occlusive crises episodes. These episodes are the result of a combination of processes including inflammation, thrombosis, and blood cell adhesion to the vascular wall which leads to blockages within the vasculature termed vaso-occlusions. Vaso-occlusive episodes deprive tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
(196 reference statements)
0
7
0
Order By: Relevance
“…22,31 However, the utility of microfluidics to risk stratify patients for postoperative thrombotic complications remain largely unexplored. Other pathologic occlusion events in disease states such as sickle cell disease, 32 tumors, 33 and cardiovascular disease 34 have been tested in in vitro models, but have not been used clinically to risk stratify patients. Recent work with computational modeling paired with microfluidic devices suggest that flow is critical for determining the risk of vascular occlusion, particularly in arterial shear rates.…”
Section: Discussionmentioning
confidence: 99%
“…22,31 However, the utility of microfluidics to risk stratify patients for postoperative thrombotic complications remain largely unexplored. Other pathologic occlusion events in disease states such as sickle cell disease, 32 tumors, 33 and cardiovascular disease 34 have been tested in in vitro models, but have not been used clinically to risk stratify patients. Recent work with computational modeling paired with microfluidic devices suggest that flow is critical for determining the risk of vascular occlusion, particularly in arterial shear rates.…”
Section: Discussionmentioning
confidence: 99%
“…Dissecting roles of RBC deformation, flow shear, distinct cell-cell interactions, adhesion activation, endothelial permeability/dysfunction, immune activation, and converging/diverging vascular bed geometry are essential to fully understand pathophysiology underlying VOC and beyond in SCD in order to develop mechanism-driven targeted therapeutics. Over the last decade, microfluidics have risen to this occasion to enable sickle cell researchers to fabricate and employ simple devices (Horton, 2017) that emulate microvascular dimensions and/or blood cell-endothelial interactions and facilitate in vitro experiments to study RBC sickling and VOC events.…”
Section: Current State-of-the Art Of Microfluidics In Sickle Cell Resmentioning
confidence: 99%
“…This figure shows some examples of application of microfluidics in studying HbS polymerization, VOC, and enhanced adhesion of sickled RBCs. (A) This was the first device that demonstrated hypoxia induced sickling alone could obstruct microvascular network and demonstrated utility of microfluidics for the study of vaso-occlusion (Horton, 2017). (B) The authors utilized high throughput microfluidic single RBC analysis to quantify sickle hemoglobin polymerization in terms of RBC oxygen saturation (Du et al, 2015).…”
Section: Devices To Study Sickle Rbc Deformability Blood Rheology Amentioning
confidence: 99%
“…13–15 It has been shown that SCD is caused by the abnormal hemoglobin polymerization of the RBC, 1,14 leading to a reduction in RBC deformability 13 as well as abnormality in RBC adhesion. 15 Microfluidic devices are a powerful tool for the analysis of factors such as red blood cell deformability and adhesiveness, 16–20 geometric variability in microcapillaries, 21–26 and changes in blood under different oxygen levels. 27–29…”
Section: Introductionmentioning
confidence: 99%